2010
DOI: 10.1177/0218492310362004
|View full text |Cite
|
Sign up to set email alerts
|

Lower Ministernotomy and Fast Tracking for Atrial Septal Defect

Abstract: We report our experience with a 3-5-cm lower ministernotomy incision for closure of atrial septal defect in 53 patients. Fibrillatory arrest was used in 19 patients, and crossclamping with cardioplegia in 33. One patient had to be converted from fibrillatory arrest to crossclamping with cardioplegic arrest. The mean bypass time was 39.6 +/- 13.1 min, arrest time was 9.9 +/- 4.5 min, and crossclamp time was 20.7 +/- 8.69 min. All patients recovered without adverse events. They were fast tracked to recovery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…In case there is a need to split the sternum more than usual, in rare cases, there may be an injury to one or more intercostal neurovascular bundles or instability in the anterior chest wall. [1,5,7] In our patients, we did not observe such complications.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In case there is a need to split the sternum more than usual, in rare cases, there may be an injury to one or more intercostal neurovascular bundles or instability in the anterior chest wall. [1,5,7] In our patients, we did not observe such complications.…”
Section: Discussioncontrasting
confidence: 45%
“…Finally, it is less painful than a minithoracotomy. [4,5] Right minithoracotomies or inframammary incisions have been supported particularly in female patients where the inframammary fold helps to cover the incision. The cosmetic results of these alternative approaches have been reported to be satisfactory, but specific complications related to the incision have been seen.…”
Section: Discussionmentioning
confidence: 99%
“…Sebastian et al [ 9 ] found no differences in the number of blood transfusions but a prolonged cardiopulmonary bypass and cross-clamp times in the ministernotomy group. The issue of increased surgical time with minimally invasive surgery is encountered not only with ministernotomy, but also with other less invasive approaches [ 5 , 8 ]. This has been explained by a smaller surgical field and a more complicated cannulation technique.…”
Section: Discussionmentioning
confidence: 99%
“…In reply to the letter of Dr Nagarajan Muthialu 1 regarding our recent paper: 2 we profusely appreciate Dr Muthialu’s opinion and valued comments. We wish to state that we do not use intraoperative transesophageal echocardiography for atrial septal defect closure on a regular basis.…”
mentioning
confidence: 92%